THE INFLUENCE OF LEARNING MOTIVATION AND PARENTAL SUPPORT ON STUDENTS' LEARNING INTERESTS AT SMP BUMI AL-QUR'AN PEMATANGSIANTAR - Roni Marwan; Salamiah Sari Dewi; Nina Siti Salmaniah Siregar (RADJA PUBLIKA, 2025)
To determine the effect of learning motivation and parental support on student interest in learning at Smp Bumi Al-Qur'an Pematang Siantar. The research method uses quantitative non-experimentation. The population in this study were 100 students, using the total sampling technique. The data analysis technique used is multiple regression analysis techniques with the assumption that the data is normally distributed and linear. The results of testing the first hypothesis are explained based on the results of regression analysis obtained a regression magnitude value of 0.93, this value is equal to 93%, meaning that there is an influence between motivation on interest in learning. The results of testing the second hypothesis obtained a regression magnitude value of 0.95, this value is equal to 95%, meaning that there is an influence between parental support on interest in learning. And the results of testing the third hypothesis obtained a regression value of 0.95, this value is equal to 95%, meaning that there is an influence between motivation and parental support on interest in learning. With this together learning motivation and parental support can affect student interest in learning